Data analytics and management in data intensive domains : 21st International Conference, DAMDID/RCDL 2019, Kazan, Russia, October 15-18, 2019, Revised Selected Papers /: 21st International Conference, DAMDID/RCDL 2019, Kazan, Russia, October 15-18, 2019, Revised Selected Papers. (2020) - Unknown
No abstract available